High thermally stable hybrid materials based on amorphous porous silicon nanoparticles and imidazolium-based ionic liquids: Structural and chemical analysis. (2021) - Tchalala, Mohamed R.; El-Demellawi, Jehad K.; Kalakonda, Parvathalu; Chaieb, Sahraoui
Abstract: Compared to conventional solvents, ionic liquids (ILs) are highly recognized for their ability to enhance the dispersion of nanoparticles (NPs). However, the thermal stability of the ILs-based nanocomposites is a vital parameter for their processing applications. Here, we scrutinized the thermal stability of a series of different imidazolium ion-based ILs before and after incorporating amorphous porous silicon (ap-Si) NPs. The results show that regardless of the obtained quality dispersion, the thermal stability of the host ILs was never regressed. The combination of ap-Si NPs and bmim-SCN (1-buthyl-3-methyl imidazolium thiocyanate) induced highly dispersed framework with an enhanced thermal stability (∼15 °C shift to higher temperature). Likewise, the emim-BF4 (1-ethyl-3-methylimidazolium tetrafluoroborate) coated the ap-Si NPs forming a very stable dispersion along with a good thermal stability (∼8 °C shift). On the other hand, the thermal stability of bmim-Ac (1-buthyl-3-methylimidazolium acetate) was not affected owing to the high viscosity of bmim-Ac that limited the dispersion of ap-Si NPs at room temperature. Throughout our study, we explored the intermolecular interactions using SEM, TEM, Raman spectroscopy and XRD. We probed the thermal stability of the fabricated dispersions using TGA, and DSC as part of characterization methodology.